2007
DOI: 10.1007/s11256-007-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers’ Perceptions of Mathematics Education in Urban Schools

Abstract: This article reports findings from a study of preservice mathematics teacher education students and their beliefs about and experiences with students in an urban high school. The preservice teacher education students participated as mentors to a group of peer tutors in a mathematics tutoring program. Data collected from questionnaires and interviews reveal that the mentors had varied perceptions of tutoring program participantsÕ motivation, interest, and knowledge of mathematics. Mentors held varied perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Preservice teachers hold many assumptions about students and schools in high‐needs contexts. These assumptions include stereotypes of urban students, including low student motivation and a lack of parental investment (Walker, ). Preservice teachers may also be unaware of different issues facing urban and rural minority students and espouse a “colorblind” approach to teaching diverse students (Walker, ).…”
Section: Preservice Teachers’ Concerns About Teaching In High‐needs Cmentioning
confidence: 99%
See 3 more Smart Citations
“…Preservice teachers hold many assumptions about students and schools in high‐needs contexts. These assumptions include stereotypes of urban students, including low student motivation and a lack of parental investment (Walker, ). Preservice teachers may also be unaware of different issues facing urban and rural minority students and espouse a “colorblind” approach to teaching diverse students (Walker, ).…”
Section: Preservice Teachers’ Concerns About Teaching In High‐needs Cmentioning
confidence: 99%
“…These assumptions include stereotypes of urban students, including low student motivation and a lack of parental investment (Walker, ). Preservice teachers may also be unaware of different issues facing urban and rural minority students and espouse a “colorblind” approach to teaching diverse students (Walker, ). Even after experiences with bilingual learners, preservice teachers assumed that English language learners (ELL) lacked motivation, grouped all ELL into a single cultural group, and voiced hopelessness for the future prospects of ELL (Glenn & Gort, ).…”
Section: Preservice Teachers’ Concerns About Teaching In High‐needs Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on urban teacher education has shown that prospective teachers have formed beliefs and perceptions of urban schools and students prior to entering an urban classroom (Breitborde 2002) that reflect stereotypes about low student motivation, low student ability, school security, and lack of parental involvement (Gilbert 1997). These beliefs are significant for mathematics teaching, in that teachers with low expectations of urban and minority students may feel that rote instruction and an emphasis on basic skills best serve them, thus denying them opportunities for engaging in powerful, critical mathematical thinking (Walker 2007). Furthermore, efforts to engage prospective mathematics teachers in sociocultural and sociopolitical contexts of mathematics and mathematics teaching, and in the role of cultural competence in effective mathematics teaching more generally, may be hampered by the belief that mathematics is culture free and objective, and thus that teaching mathematics need not attend to issues such as race, culture, class, gender, or language (Rousseau and Tate 2003).…”
Section: Introductionmentioning
confidence: 99%